Verification of the Bühlmann fPELA turbo faecal elastase assay on the Binding Site Optilite benchtop analyser. (January 2023) - Handley, Simon A; Dote, Nikko P; Wanandy, Troy; Prentice, Louise
Background: Pancreatic elastase-1 (PE1) can be measured to assess exocrine activity of the pancreas. A semi-automated particle-enhanced, open-channel turbidimetric immunoassay has been introduced by Bühlmann (fPELA turbo, Bühlmann Laboratories AG, Schoenenbuch, Switzerland). Published evaluation data is lacking. We therefore verified performance of the assay on the Binding Site Optilite benchtop analyser and undertook a sample comparison with the DiaSorin PE1 assay on the Liaison. Methods: Accuracy, imprecision, lower limit of quantitation (LLoQ) and linearity of the Bühlmann fPELA turbo assay on the Binding Site Optilite analyser was ascertained. Comparison with the DiaSorin Liaison PE1 assay was also undertaken. Difference between assays was evaluated using the Wilcoxon signed-rank test and method comparison was undertaken using Spearman's rank correlation (rs), Bland–Altman and Passing–Bablok regression analyses. Results: The fPELA turbo assay was linear between 5 and 2500 μg/g. The LLoQ was 5 µg/g. Intra- and inter-assay imprecision was <6%. There was a good agreement (rs = 0.92) and no significant bias (5.8 µg/g, P = 0.29) present between the Bühlmann fPELA turbo and DiaSorin PE1 assays. Conclusion: The Bühlmann fPELA turbo assay performs well on the Binding Site Optilite analyser. Faecal elastase results are commutable between with Bühlmann fPELA turbo and DiaSorin Liaison PE1 assays.